Global English and political economy - O'Regan, John P. (London : Routledge, 2021)
In this book, John O'Regan examines the role of political economy in the worldwide spread of English and traces the origins and development of the dominance of English to the endless accumulation of capital in a capitalist world-system. O'Regan combines Marxist perspectives of capital accumulation with world-systems analysis, international political economy, and studies of imperialism and empire to present a historical account of the 'free riding' of English upon the global capital networks of the capitalist world-system. Relevant disciplinary perspectives on global English are examined in this light, including superdiversity, translanguaging, translingual practice, trans-spatiality, language commodification, World Englishes and English as a Lingua Franca. Global English and Political Economy presents an original historical and interdisciplinary interpretation of the global ascent of English, while also raising important theoretical and practical questions for perspectives which suggest that the time of the traditional models of English is past. Providing an introduction to key theoretical perspectives in political economy, this book is essential reading for advanced students and researchers in applied linguistics, World Englishes and related fields of study.
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Political aspects; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics